Adaptation for Survival in Nature in The Call of the Wild by Jack London and The Old Man and the Sea by Earnest Hemingway = Thích Nghi Để Tồn Tại Trong Thiên Nhiên Trong Tác Phẩm Tiếng Gọi Nơi Hoang Dã của Jack London và Ông Già Và Biển Cả của Earnest Hemingway - Trương, Thanh Thủy (2020)
Adaptation for Survival in Nature is conducted with an aim of unearthing the adaptation metamorphosis of the sled dog in The Call of the Wild by Jack London and the fisherman in The Old Man and the Sea by Earnest Hemingway. These characters’ existence in nature results from the restoration of their primordial instincts, which used to be an imperative part of human survival in ancient time. Their sensation to the nature grows exquisitely and their self- protection instinct becomes mighty in an attempt to change to fit to the environment. Though the wilderness is full of hostility and brutality, it is important to nurture the compassion, as in which the survival become more meaningful. Due to the affection, both the old man and the sled dog in the mentioned novellas are aware of its essence and find out unforgettable moments in their life, and they strive for it every time its appearance is opportune. Through a wide range of materials like books, journals or articles, this paper extends a vision on theses classics under the theory of ecocriticism. The creatures’ survival struggle is put in the nature-centered perspective, leading to necessary adaptation strategies against the natural harshness. Though limitation is unavoidable, this paper is fulfilled at the best of the writer’s ability to make a contribution to the new literary discipline.